2015
DOI: 10.4102/curationis.v38i2.1495
|View full text |Cite
|
Sign up to set email alerts
|

Allopathic and traditional health practitioners’ collaboration

Abstract: BackgroundProfessional collaboration between traditional and allopathic health practitioners in South Africa is proposed in the Traditional Health Practitioners Act and could benefit and complement healthcare delivery.ObjectivesTo explore and describe the collaborative relationship between allopathic and traditional health practitioners regarding the legalisation of traditional healing, and these health practitioners’ views of their collaborative and professional relationship, as role-players in the healthcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…This confirmed the view of [7] onthe issue of untidiness, such as unscientific methods of traditional medicine, lack of hand washing, non-sterile equipment, and lack of measured prescription of traditional medicine according to age and weight of the patient. Patients consulting the African indigenous health practitioners resulted in complications such as diarrhoea, dehydration, poisoning and sores on the body.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This confirmed the view of [7] onthe issue of untidiness, such as unscientific methods of traditional medicine, lack of hand washing, non-sterile equipment, and lack of measured prescription of traditional medicine according to age and weight of the patient. Patients consulting the African indigenous health practitioners resulted in complications such as diarrhoea, dehydration, poisoning and sores on the body.…”
Section: Discussionsupporting
confidence: 67%
“…According to [7], mutual understanding between biomedical health and the African indigenous health practitioners was viewed as central and crucial to effective collaboration. To increase acceptance and understanding of their capabilities between thetwo types, participants indicated that they would meet together to resolvedifferences for the smooth running of the service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and their drugs affordable as compared to modern medicine [32]. Cooperation between traditional and allopathic practitioners is touted to be beneficial and complementary to health care delivery but often derailed by suspicion [33]. On drug management, toxicity (hepatoxicity and cardiotoxicity) cases in traditional medicine use has been reported though not widely documented [6,25,34].…”
Section: Convention On Biological Diversity United Nations 1992mentioning
confidence: 99%
“…The study used a purposive sampling with elements of snow ball in the selection of the key respondents who then recruited other competent respondents into the survey [3,33,71]. All willing respondents were interviewed after obtaining an oral prior informed consent.…”
Section: Study Areamentioning
confidence: 99%